Analisis Efisiensi Pembuatan Tas Bordir Aceh(Studi Kasus di Kecamatan Muara Batu Kabupaten Aceh Utara) - Nova Yani; Hijri Juliansyah (LPPM UNIMAL, 2021)
This study aims to analyze and find out how much the level of efficiency in making Aceh embroidery bags (Case Study in Muara Batu District, North Aceh Regency). The data used in this study are primary data obtained from 20 Aceh embroidery bag business units. This research uses Data Envelopment Analysis (DEA) method. From the Constant Return to Scale (CRS - Output Oriented), results showed that only four business units were efficient while sixteen business units were inefficient. Through the results of Variable Return to Scale (VRS - output oriented), there were seven efficient business units, while thirteen more business units were inefficient.Keywords:Data Envelopment Analysis (DEA), Efficiency, CRS, VRS, Output Oriented